Creating shared value through implementing vocational rehabilitation in the corporate social responsibility strategy: A literature review - Boris Miethlich; Ľudomír Šlahor (Vision 2020: Sustainable Economic Development and Application of Innovation Management, 32nd International Business Information Management Association Conference (IBIMA), Seville, 15-16.11.2018, 2018)
After an accident or illness, it may be difficult or even impossible to return to work. Although occupational safety and health (OHS) are essential elements of corporate social responsibility (CSR), support for employees returning to work or vocational rehabilitation are rarely part of the CSR strategy. The aim of this paper is to assess and synthesize the current state of research of vocational rehabilitation in the context of CSR. A literature analysis was conducted to examine the need to address vocational rehabilitation as part of the CSR strategy as well as the existing approaches for implementation. Vocational rehabilitation is an important part of a company's social responsibility towards its employees as well as towards society. The promotion of vocational rehabilitation should be an essential element of the CSR strategy and can create shared value. However, a commitment to vocational rehabilitation alone is not enough; the commitment must be explicitly described and go beyond the legal minimum. That can be done, for example, through return-to-work (RTW) policies, proactive initiation and coordination of the rehabilitation process, the adaptation of the workplace and work activities, the institutionalization of sheltered workplaces, and a specialist unit for vocational rehabilitation within the company. Particularly access for external persons to the company's sheltered workplaces, internships or entry-level positions is a critical aspect for substantially promoting vocational rehabilitation and achieving additional shared value. Vocational rehabilitation as part of the CSR strategy must continue to be examined empirically, in particular "best practice" approaches from business practice. – – Nach einem Unfall oder Krankheit kann die Rückkehr an den Arbeitsplatz, schwierig oder gar unmöglich werden. Obwohl Arbeitsschutz und betriebliche Gesundheit zentrale Elemente der sozialen Unternehmensverantwortung (CSR) sind, ist die Unterstützung der Mitarbeiter bei der Rückkehr in die Arbeit bzw. der beruflichen Rehabilitation nur selten Teil der CSR-Strategie. Dieses Paper untersucht anhand einer Literaturanalyse die Ansätze zur Implementierung als auch die Notwendigkeit die berufliche Rehabilitation als Teil der CSR-Strategie anzusprechen. Die berufliche Rehabilitation ist ein wichtiger Teil der sozialen Verantwortung eines Unternehmens gegenüber seinen Mitarbeitern und somit gegenüber der Gesellschaft. Die Förderung der beruflichen Rehabilitation stellt ein wichtiges Element der CSR-Strategie dar und kann einen gemeinsamen Mehrwert schaffen. Ein Bekenntnis zur beruflichen Rehabilitation alleine reicht jedoch nicht aus, das Engagement muss explizit beschrieben werden und über das gesetzliche Minimum hinausgehen. Das kann beispielsweise mittels «Return to Work» (RTW) Richtlinien, proaktiver Initiierung und Koordination des Rehabilitations-Prozesses, dem Anpassen von Arbeitsplatz und Arbeitstätigkeiten, dem institutionalisieren von Schonarbeitsplätzen und einer Fachstelle für berufliche Rehabilitation innerhalb des Unternehmens erfolgen. Insbesondere der Zugang für externe Personen zu den Unternehmenseigenen Schonarbeitsplätzen, Praktikas oder Einstiegspositionen ist ein wichtiger Aspekt, um die berufliche Rehabilitation wesentlich zu fördern und einen zusätzlichen gemeinsamen Mehrwert zu erzielen. Die berufliche Rehabilitation als Teil der CSR-Strategie muss weiter empirisch untersucht werden. Insbesondere fehlen «Best practice» Ansätze aus der Unternehmenspraxis.
Keywords: J14; M14; I18; 330; vocational rehabilitation; disability management; shared value; CSR